Analysis of enablers on the successful implementation of green manufacturing for Irish SMEs. Issue 1 (24th August 2020) - Ghadimi, Pezhman; O'Neill, Shane; Wang, Chao; Sutherland, John W.
Abstract : Purpose: The purpose of this study is to identify a comprehensive list of main enablers of successful implementation of green manufacturing (GM) practices in small and medium-sized enterprises (SMEs). Based on the inputs from Irish SMEs' experts, a validated conceptual hierarchy model of the identified enablers is developed to analyse and prioritise the most dominant ones. Design/methodology/approach: Data were collected using a questionnaire survey responded by various professionals in Irish manufacturing SMEs. Experts' opinions were analysed using interpretive structural modelling (ISM) and cross-impact matrix multiplication applied to classification (MICMAC) to distinguish the mutual influences amongst the nine identified enablers. Findings: The findings revealed that from the Irish SMEs' perspective, strong green supply chain relations are the outcome of successfully implementing GM and not a driver of the other enablers. Furthermore, lower manufacturing costs are found to arise as a result of GM practices in SMEs. Practical implications: It is discussed that emulating the actions of larger companies will not necessarily yield the same results for SMEs. Innovation will become a cornerstone of remaining competitive in a sustainable environment, which is facilitated by closer green supply chain relations. Originality/value: The reported findings in this article contribute to theory and practice of GM and SMEs research domains by systematically identified, classified and ranked enablers in a conceptual hierarchal model from the perspective of Irish SMEs. This research lays the foundations for further analysis of the GM practices enablers in a time when UN mandates and EU regulations are increasingly impacting SMEs all around Europe and especially Ireland.